Kesultanan Nusantara dan Faham Keagamaan Moderat di Indonesia - Choirul Fuad Yusuf (Jurnal Lektur Keagamaan, 2016)
The Sultanates (Islamic kingdoms), have played a pivotal role in the spread of Islamic teachings throughout the Nusantara archipelago – the archipelago that was later to be known as Indonesia. This article tries to trace and explain the most significant contribution of the Sultanates in spreading Islamic teaching around the archipelago. With the use of documentary method, the article highlights some conclusions. First, the Sultantes played an important role in the process of Islamization in the Nusantare archipelago. Through their political authority or influences, most of Sultans involved proactively in the process of spreading Islam in Indonesia—at least by implementing policies for Islamic development. Second, doctrinarily, most of Nusantara (Indonesia) Sultanates developed a moderate Islam which was significantly able to be witnessed up to the present time. Any cultural capitals of the pre-Islamic society and the powerful authority of Sultanates in one side, and the characters of Islam itself as a universal religion in another side, a moderate Islamic teachings has significantly developed with its great influnces in a wider aspect of life in Indonesia today. Key words: sultanate, spread of Islam, radical Islam, moderate teachings, future Islam. Kesultanan memegang peranan sangat penting dan strategis dalam penyebaran Islam di Nusantara (Indonesia), terutama pada awal perkembangannya. Artikel ini mencoba untuk menelusuri, apa dan sejauhmana peranan yang dilakukan kesultanan atau kerajaan Islam dalam proses penyebaran dan penguatan Islam di Nusantara. Dengan menggunakan pendekatan studi dokumen ini, tulisan ini menggaris-bawahi sejumlah kesimpulan. Pertama, Kesultanan Nusantara memegang peran penting dan strategis dalam penyebaran, pengembangan Islam proses Islamisasi di wilayah Nusantara (baca: Indonesia). Melalui pengaruh politis otoritarian, Sultan atau raja, membantu percepatan penyebaran dan pengembangan ajaran Islam Indonesia. Kedua, secara doktrinal, sebagian besar kesultanan Nusantara mengembangkan ajaran Islam moderat. Modal kultural masyarakat Indonesias pra-Islam, dan peranan Kesultanan yang otoritatif di satu pihak dan karakteristik ajaran islam moderat yang masuk ke Indonesia pada saat itu di pihak lain, Islam moderat mengalami perkem¬bangan yang sangat cepat dan efektif sehingga pengaruhnya dapat dirasa-kan hingga dewasa ini pada berbagai aspek kehidupan. Kata Kunci: Kesultanan, penyebaran Islam, Islam radikal, ajaran moderat, Islam Masa depan.